Pengaruh Pemasaran Afiliasi dan Ulasan Online dalam Keputusan Pembelian - Chelsea Halim, Kimberly; Valeron Chandra, Enrico; Tristan Lie, Miko; muchtar, muchtar (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2025)
This study aims to determine the influence of affiliate marketing and online reviews on consumer purchasing decisions on the Shopee marketplace. A quantitative approach was employed using a survey method, in which data were collected through questionnaires distributed to 100 respondents who are active Shopee users. The data were analyzed using multiple linear regression to examine both the simultaneous and partial effects of the independent variables on the dependent variable. The results show that both affiliate marketing and online reviews have a positive and significant influence on purchasing decisions, both simultaneously and partially. These findings indicate that digital strategies through affiliate programs and online reviews are crucial factors in enhancing consumer purchasing decisions on e-commerce platforms.